Caspase 3-mediated cytotoxicity of mealworm larvae (Tenebrio molitor) oil extract against human hepatocellular carcinoma and colorectal adenocarcinoma. (25th March 2020) - Wu, Ricardo A.; Ding, Qingzhi; Lu, Huijia; Tan, Haochen; Sun, Nianzhen; Wang, Kai; He, Ronghai; Luo, Lin; Ma, Haile; Li, Zhikun
Abstract: Ethnopharmacological relevance: Mealworm larvae (MWL) ( Tenebrio molitor ) have been traditionally used in Asian countries for the treatment of liver diseases, including cancer. However, to date, there is marginal information on the mechanisms underlying the anticancer activity of MWL oil. Aim of the study: This study aims to determine the in vitro effect of MWL oil on human hepatocellular carcinoma (HepG2) and colorectal adenocarcinoma (Caco-2) cells growth in order to produce insect-derived chemotherapeutic agents against cancer. Materials and methods: MWL oil was extracted, and its effects on cancer cells growth were investigated, by the MTT reduction, AO/EB staining, Hoechst 33258 nuclear staining, apoptosis, comet, and caspase activity assays. Results: MWL oil inhibited HepG2 and Caco-2 growth, with IC50 (48 h) values of 0.98% for HepG2 and 0.37% for Caco-2 cells. In addition, flow cytometry analysis demonstrated that 24 h-MWL oil treatment increased early and late apoptosis from 0.04% to 39.77% and from 2.06% to 74.34% on HepG2 and Caco-2 cells, respectively. The mechanism of apoptosis was associated with the death receptor pathway by the activation of caspases -8, -9, and -3, and correlated to its fatty acids action. Conclusion: Results of this study demonstrated the potential of MWL oil in the development of natural anticancer therapeutic agents. Graphical abstract: Image 1